Development of Web-based School Uniforms order Application in a Private School with Prototyping Model - Wiratama, Jansen; Ady Sanjaya, Samuel; Santoso, Hari; Brian Kurniadi, Reinardus (International Journal of Science, Technology & Management, 2023)
Strada SMK Daan Mogot, a private school in Tangerang City, oversees several operations. Student registration, academic exams, uniform measurements, and book purchases are carried out at the beginning of each school year. The Uniform Team tasked with handling this activity experienced difficulties due to the large volume of data, making conventional techniques inefficient to carry out. This research focuses on simplifying uniform ordering procedures from the uniform team to the uniform manufacturing supplier. The Uniform Team recorded and measured orders by hand, which resulted in time-consuming management and limited real-time data monitoring for the Principal. A web-based solution that allows easy access to uniform ordering data is needed to speed up these operations. The successful development and installation of this application at SMK Strada Daan Mogot is a significant achievement, with good User Acceptance Test results and confirming alignment with user needs. This progress is an essential step toward optimizing school operations.